HUBUNGAN SANITASI LINGKUNGAN DENGAN KEJADIAN INFEKSI SALURAN PERNAFASAN AKUT (ISPA) PADA BALITA DI DESA MARENDAL I PASAR V KAB. DELI SERDANG TAHUN 2018 - Nurmala Sari; Diana Rahmadani Siregar (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2019)
Infection of exhalation Acude (ISPA), is one of the main painfulness because for children under five years old in developing countries. The aims of this research was to know the relationship between environmental sanitation forincluded houseventilation, air pollution, andaccupancydensity. The conducted of this research in November 2018 in Marendal I Pasar V Deli Serdang. Regency theobservational research with cross sectional approach. The subject were all of the house which have children under five years old with 54 respondents sample. The technique of sample used cluster random sampling.The statistical test used chi square test by using Statistical product and service solutions version 20 program. The resultof this research indicated that there was a relationship between house ventilation,air pollution and accupancy density with the occurrence of ISPA (Infection of exhalation Acude). Poor ventilation can cause high humidity and endanger health so that the incidence of Infection of exhalation Acude will increase. The condition of a dense residence can increase the air pollution factor in the house. And the floor area of a healthy home building must be enough for the residents inside. The area of a building that is not proportional to the number of occupants can cause easy disease. lack of oxygen, dirty air can invite various chemicals so it is easy to trigger the disease that comes, Every citizen is expected to always pay attention and try so that his house meets health requirements such as house ventilation, residential density in the bedroom, and healthy air pollution.